2018
DOI: 10.1088/1361-6455/aaf060
|View full text |Cite
|
Sign up to set email alerts
|

He-ion induced surface morphology change and nanofuzz growth on hot tungsten surfaces

Abstract: Tungsten has been recently chosen as the divertor material in ITER and is a leading candidate for use in DEMO and future fusion reactors. Linear plasma device and laboratory experiments have shown substantial nanostructured surface modification in tungsten, of low-density ‘fuzz’-like appearance, when exposed to helium ions with impact energies that are below the displacement damage and sputtering thresholds for tungsten, and under temperature and ion flux conditions likely to be encountered in such fusion devi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 162 publications
(108 reference statements)
1
9
0
Order By: Relevance
“…It would also be useful to see if there is a different thickness-fluence relationship at very high fuzz thicknesses if the mechanism changes. Meyer [8] speculates whether adatoms would be generated midway upon tendril sides instead of at the base. To avoid the long times needed for this, tungsten deposition (see Sect.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It would also be useful to see if there is a different thickness-fluence relationship at very high fuzz thicknesses if the mechanism changes. Meyer [8] speculates whether adatoms would be generated midway upon tendril sides instead of at the base. To avoid the long times needed for this, tungsten deposition (see Sect.…”
Section: Discussionmentioning
confidence: 99%
“…4, a large concentration of atoms from the bulk would not be seen at the edges of tendrils. During late-stage growth, bubbles within the fuzz could also lead to adatom formation on the side of tendrils by the same mechanism [8].…”
Section: Adatom Diffusionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although a number of additional mechanisms have been proposed to play a role in formation of space weathering textures, including micrometeoroid impacts (Loeffler et al., 2016; Sasaki et al., 2001) and other sources of heating (Thompson et al., 2017), irradiation of surfaces by solar‐wind ions is considered the principal weathering mechanism on asteroids (Schläppi et al., 2008), directly linked to the formation of npFe and iron‐cladding on exposed surfaces (Matsumoto et al., 2020; Noguchi et al., 2014). Moreover, research on metals and oxides has identified other damage modes associated with light‐ion irradiation at energies similar to solar‐wind ions, such as phase‐change, pitting, and blistering (Auciello, 1984; Kajita et al., 2016; Meyer, 2018; Tanyeli et al., 2015).…”
Section: Introductionmentioning
confidence: 99%